2010
DOI: 10.1590/s0034-89102010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à realização de cesariana em hospitais brasileiros

Abstract: OBJECTIVE:To assess the prevalence of cesarean sections in Brazilian hospitals. METHODS: RESULTS:The prevalence ratio of cesarean sections was significantly higher among older women, who were married/living with a partner and with higher body mass index. The following conditions during pregnancy or birth were associated with higher cesarean section prevalence ratio: parturient being diagnosed as HIV-positive, heavier weight and greater head circumference of the newborn, and more prenatal consultations. In reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
42

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 20 publications
3
35
0
42
Order By: Relevance
“…Associations between mode of delivery and adverse pregnancy outcome may sometimes be difficult to interpret given the possibility of reverse causality. For example, there is a strong association between maternal morbidity, such as vaginal bleeding and high blood pressure during pregnancy, and cesarean section 32 . Cesarean section may act as a protective factor against adverse pregnancy outcomes, resulting in benefits to mothers and newborns 32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between mode of delivery and adverse pregnancy outcome may sometimes be difficult to interpret given the possibility of reverse causality. For example, there is a strong association between maternal morbidity, such as vaginal bleeding and high blood pressure during pregnancy, and cesarean section 32 . Cesarean section may act as a protective factor against adverse pregnancy outcomes, resulting in benefits to mothers and newborns 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is a strong association between maternal morbidity, such as vaginal bleeding and high blood pressure during pregnancy, and cesarean section 32 . Cesarean section may act as a protective factor against adverse pregnancy outcomes, resulting in benefits to mothers and newborns 32,33 . In contrast, cesarean section on demand can be a risk factor for adverse perinatal outcomes like prematurity 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sec onal study performed in three Brazilian ci es revealed that the rate of opera ve delivery is higher in women of a more advanced age, with the prevalence rate of Cesarean sec ons among 35 yearold women being twice that observed in those less than 20 years of age. A stable rela onship, high levels of educa on and high number of antenatal consulta ons were also associated with this surgery (18) . It should be emphasized that, in all the mul parous women assisted at home (13) , eight had had previous Cesarean sec ons, and three of them underwent this procedure again.…”
Section: Discussionmentioning
confidence: 82%
“…This is lower than the rate of 15% reported by the World Health Organiza on (17) and is congruent with that found in the majority of studies that show percentages between 5.2% and 28.6% (3,5,(8)(9)11) , being more frequent among nulliparous women (5,14) . It was observed that not all the transferred women underwent a Cesarean sec on; those who did, presented with similar sociodemographic characteris cs to those assisted at the hospital who underwent the same surgical procedure (18) . A cross-sec onal study performed in three Brazilian ci es revealed that the rate of opera ve delivery is higher in women of a more advanced age, with the prevalence rate of Cesarean sec ons among 35 yearold women being twice that observed in those less than 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…(BRASIL, 2014a CAMARA; MEDEIROS; BARBOSA, 2000;DOMINGUES et al, 2014;PADUA et al, 2010;ROCHA;ORTIZ;FUNG, 1985;YAZLLE et al, 2001).…”
Section: Leis Projetos De Leis Decretos E Portariasmentioning
confidence: 99%